2020
DOI: 10.1002/anie.202011835
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Synthetic Modification: Systematic Study on a Simple Access to Nitridophosphates

Abstract: Nitridophosphates are a well-studied class of nitrides with diverse materials properties, such as luminescence or ion conductivity. Despite the growing interest in this compound class, their synthesis mostly works through direct combination of starting materials. Herein, we present a systematic study on a promising method for post-synthetic modification by treating pre-synthesized nitridophosphates with halides under elevated pressures and temperatures. Herein, we focus on the applicability of this approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Since magnesium participates in the tetrahedral anionic framework as a NFC, AE 3 [Mg 2 P 10 N 20 ] exhibits the hitherto highest degree of condensation in multinary nitridophosphates, with k = n(NFC) : n(N) = 0.6 (k max, obs = 0.57 in HP 4 N 7 , MP 4 N 7 (M = Li, Na, K, Rb, Cs), AEP 8 N 14 (AE = Mg, Ca, Sr, Ba). [9,[17][18][19][20] The anionic 3D framework of the crystal structure is based of all-side vertex-sharing Q 4type MgN [3] 4 , PN [2] 3 N [3] and PN [2] 2 N [3] 2 tetrahedra (superscripted coordination numbers in square brackets, Figure 1A). Focusing only on the P/N framework, two striking structural motifs become apparent.…”
Section: Resultsmentioning
confidence: 99%
“…Since magnesium participates in the tetrahedral anionic framework as a NFC, AE 3 [Mg 2 P 10 N 20 ] exhibits the hitherto highest degree of condensation in multinary nitridophosphates, with k = n(NFC) : n(N) = 0.6 (k max, obs = 0.57 in HP 4 N 7 , MP 4 N 7 (M = Li, Na, K, Rb, Cs), AEP 8 N 14 (AE = Mg, Ca, Sr, Ba). [9,[17][18][19][20] The anionic 3D framework of the crystal structure is based of all-side vertex-sharing Q 4type MgN [3] 4 , PN [2] 3 N [3] and PN [2] 2 N [3] 2 tetrahedra (superscripted coordination numbers in square brackets, Figure 1A). Focusing only on the P/N framework, two striking structural motifs become apparent.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained MgP 8 N 14 has previously not been accessible by conventional synthesis and its structure was now elucidated from powder diffraction data, with a detailed discussion provided in the Supporting Information ( Figures S8 and S9, Table S7). [36] The closely similar structures of AEP 8 N 14 (AE = Mg, Ca) indicate a topotactic reaction, which might be realized through the highly-condensed quadruple layers of CaP 8 N 14 with (k = 0.57). Thus, the PN 4 tetrahedra layers are assumed to be rather rigid, while Ca 2+ ions in between remain mobile and easily accessible.…”
mentioning
confidence: 90%
“…38 Transferring the well-known ion exchange to high-pressure, high-temperature syntheses, it was shown that a preservation of a P/N framework is possible. 46 Recently, in situ-generated HCl and HF were used to activate inert starting materials such as BN or even TiN. 43,44 It is assumed that reactive intermediate species are formed during the reaction process.…”
Section: ■ Introductionmentioning
confidence: 99%